Behavior as a stereotype cue: An European Portuguese pretest on age and gender stereotypes - Cipriano, M. (2021)
When it comes to the study of stereotypes, plenty of material can be of use. While personality traits tend to be the most commonly adopted, behavioral information can also be relevant, both in the study of stereotypes, as well as in other research fields (e.g., illusory correlations, memory and judgement and decision making). The purpose of this paper was to create a readily available list of behavioral sentences with stereotypicality ratings for both age (young to old) and gender (woman to man) categories, to be used in future studies. In two studies, participants judged age and gender stereotypicality of more than two hundred sentences in European Portuguese. Results were stable across both studies, using different methodologies (three alternative forced-choice task, in Study 1; bipolar rating scale, in Study 2). Relative frequencies for each choice, as well as average ratings, per behavior, are provided at the end.